Innovation, trade and multi‐product firms. (28th February 2021) - Montinari, Letizia; Riccaboni, Massimo; Schiavo, Stefano
Abstract: This paper contributes to the literature on the relationship between innovation and exports by developing a model that emphasizes the role of product innovation in explaining heterogeneity in export behaviour both across and within firms. The dynamic model assumes that firms invest to maintain and increase the portfolio of products they sell: innovation is a stochastic process whereby the probability to capture new business opportunities is a function of the number of goods already sold. Crucially, the model assumes two independent mechanisms to drive the extensive and the intensive margins of a firm's export. The resulting lack of (built‐in) correlation between the two margins is well reflected in the data and represents the main contribution of our theoretical framework. The model is consistent with several other empirical regularities that characterize multi‐product firms, such as the heavy tail in the distribution of the number of products exported by each firm, the strict hierarchy in the sales of products across markets, the substantial degree of product churning and the highly skewed distributions of export sales. Résumé: Innovation, commerce et entreprises pluriproductrices . En matière de rapport entre innovation et exportation, et afin d'expliquer l'hétérogénéité des comportements d'exportations à la fois entre et au sein même des entreprises, notre article apporte une contribution à la littérature existante en développant un modèle soulignant l'importance de l'innovation. Ce modèle dynamique suppose que les entreprises investissent dans le but de maintenir et d'accroître leur gamme de produits: l'innovation est donc un processus stochastique où la probabilité de saisir de nouveaux débouchés commerciaux dépend du volume de produits déjà vendus. Dans une large mesure, ce modèle suppose deux mécanismes indépendants permettant de générer les marges intensives et extensives des exportations d'une entreprise. L'absence de lien entre les deux marges transparaît dans nos données, constituant ainsi la contribution principale à notre cadre théorique. Ce modèle est conforme à d'autres régularités empiriques caractéristiques des entreprises pluriproductrices, notamment une distribution à queue lourde par rapport au nombre de produits exportés par chaque entreprise, une stricte hiérarchie des ventes de produits sur les marchés, un degré élevé d'introduction de nouveaux produits et une distribution très inégale des ventes à l'exportation.